Slow and fast surface electromagnetic waves in planar structures contained left-handed material - Galaydych, V.K.; Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2015)
It was studied the properties of electromagnetic surface waves in left-handed material slab bounded by two semi-infinite nonmagnetic media with frequency dependent positive permittivity. It was assumed that all these media are isotropic and non-dissipative. It was shown that the phase velocities of waves are greater than the speed of light, and the group velocities are zero or negative. Вивчені властивості поверхневих електромагнітних хвиль, що поширюються уздовж шару лівостороннього матеріалу, обмеженого двома напівнескінченими немагнітними середовищами з додатними діелектричними проникностями, що залежать від частоти. Вважалось, що всі середовища є ізотропними та в них відсутні втрати. Показано, що фазові швидкості розглянутих хвиль можуть бути більше швидкості світла, а групові – нульовими або від’ємними. Изучены свойства поверхностных электромагнитных волн, распространяющихся вдоль слоя левостороннего материала, ограниченного двумя полубесконечными немагнитными средами с положительными диэлектрическими проницаемостями, зависящими от частоты. Предполагалось, что все среды являются изотропны и в них отсутствуют потери. Показано, что фазовые скорости рассматриваемых волн могут быть больше скорости света, а групповые – нулевыми или отрицательными.